(untitled) (Research, Society and Development, 2020)
Objective: Develop and validate a diagnostic tool of temporomandibular disorders (TMD) compared to the gold standard (RDC/TMD). Methods: Construction and validation of the questionnaire followed a series of steps: test validation, face validity, factorial validity and validation in comparison to the gold standard. Stability of the questionnaires with 5 and 7 items was tested by Intraclass Correlation Coefficient. Results: 130 individuals participated for the factorial validation and 99 for the validation in comparison to the gold standard. The instrument stability was 0.923 for both questionnaires. Considering the total score of the questions for the questionnaire with 7 items, the best result for TMD was assumed for scores from 10 to 21, while 85.1% was also positive in RDC/TMD. Scores from 7 to 9 revealed no TMD, and 96.2% was also negative in RDC/TMD with accuracy of 90.1%. Sensitivity was 95% and specificity 87%. For the questionnaire with 5 items, the best result for TMD was assumed for scores from 7 to 15 while no TMD was associated to scores 5 and 6, with accuracy of 85.8%. Sensitivity was 88% and specificity 84%. Conclusion: Simple and fast questionnaires with reliability for the diagnosis of temporomandibular disorder were obtained.